UV Spectral Studies in Protonation of Cu-Phthalocyanine and Phthalocyanine in Sulphuric Acid-Solvent - Srivastava, K.P.; Kumar, A. (Asian Journal of Chemistry, 2010)
Our studies in protonation of phthalocyanine (H2Pc) with sulphuric acid remove the controversy concerning its degree of protonation. The absorption spectra of phthalocyanine (H0Pc) and Cu-phthalocyanine (CuPc) have been used to illustrate the effect of electronic nature of coordinated metal, its protonation depth and position of bands in sulphuric acid medium. The CuPc and its ligand H2Pc absorb 786 nm and 754 nm respectively in sulphuric acid. The position of bands of H2Pc and CuPc in electronic absorption spectra do not seem to depend upon the sulphuric acid concentration and remain the same even in 100% H2SO4. This obviously indicates that CuPc and H2Pc both yield a single protonated form in sulphuric acid. The spectral changes during the protonation are almost the same. This is clear indication of the same type of proton attachment and the same site of its localization.